Pre-incarceration police harassment, drug addiction and HIV risk behaviours among prisoners in Kyrgyzstan and Azerbaijan: results from a nationally representative cross-sectional study. - Polonsky, Maxim; Azbel, Lyuba; Wegman, Martin P; Izenberg, Jacob M; Bachireddy, Chethan; Wickersham, Jeffrey A; Dvoriak, Sergii; Altice, Frederick L (Journal of the International AIDS Society, 2016)
The expanding HIV epidemic in Azerbaijan and Kyrgyzstan is concentrated among people who inject drugs (PWID), who comprise a third of prisoners there. Detention of PWID is common but its impact on health has not been previously studied in the region. We aimed to understand the relationship between official and unofficial (police harassment) detention of PWID and HIV risk behaviours.